2019
DOI: 10.1021/acs.macromol.9b00766
|View full text |Cite
|
Sign up to set email alerts
|

Shell Architecture Strongly Influences the Glass Transition, Surface Mobility, and Elasticity of Polymer Core-Shell Nanoparticles

Abstract: Despite the growing application of nanostructured polymeric materials, there still remains a large gap in our understanding of polymer mechanics and thermal stability under confinement and near polymer–polymer interfaces. In particular, the knowledge of polymer nanoparticle thermal stability and mechanics is of great importance for their application in drug delivery, phononics, and photonics. Here, we quantified the effects of a polymer shell layer on the modulus and glass-transition temperature ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…We further confirmed the formation and stability of irreversibly absorbed layers atop the NPs via BLS, a labelfree, contactless, nondestructive technique which probes highfrequency NP elastic vibrations. 49 In accordance with previous studies of soft core−thin shell polymer NPs, BLS measurements of colloidal clusters of PS/SiO x shell−core NPs indicated that the quadrupolar (1, 2) mode 58,59 denoting shearing motion on the NP surfacewas sensitive to NP surface dynamics. Figure 3a shows the evolution of the BLS I(f) spectrum as a function of t ann .…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…We further confirmed the formation and stability of irreversibly absorbed layers atop the NPs via BLS, a labelfree, contactless, nondestructive technique which probes highfrequency NP elastic vibrations. 49 In accordance with previous studies of soft core−thin shell polymer NPs, BLS measurements of colloidal clusters of PS/SiO x shell−core NPs indicated that the quadrupolar (1, 2) mode 58,59 denoting shearing motion on the NP surfacewas sensitive to NP surface dynamics. Figure 3a shows the evolution of the BLS I(f) spectrum as a function of t ann .…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…Glassy–rubbery interfaces between polymer domains impart material toughness and flexibility , and can be used to tune phononic transport . Although a range of different processing methods have been developed to create morphologies with sub-100 nm domain sizes, studies of simplified systems with a single interface can directly inform the underlying mechanisms behind such applications by mapping local properties as a function of distance from the interface.…”
mentioning
confidence: 99%
“…Spheres with diameter 150 nm fulfil this criterion as extensively discussed in the Supplemental Material [40], which includes Refs. [45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Characterizing the time evolution of the enthalpy, that is, the energy at constant pressure, in terms of T f during physical aging by means of differential scanning calorimetry (DSC), we find that accessing low energy states well below T g is triggered by a fast mechanism of equilibrium recovery, widely characterized in recent years [12,59,60].…”
mentioning
confidence: 86%